2021
DOI: 10.1177/23779608211064374
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disorders During COVID-19 Pandemic Among Southwest Ethiopia University Students: An Institutional-Based Cross-Sectional Study

Abstract: Introduction Coronavirus disease 2019 (COVID-19) outbreak originated in Wuhan, Hubei Province, China, at the end of 2019. The COVID-19 incidence of new cases and fatality has continued to fast-track. The mental state and well-being of entire societies are severely suffering from this crisis and are a precedence to be immediately addressed. Objective To assess mental health disorders during the COVID-19 pandemic among university students, Southwest, Ethiopia, 2020/2021. Method Institutional-based cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
2
8
1
Order By: Relevance
“…The overall prevalence of depressive symptoms was found to be 37.6%. This figure is higher than previous reports from Ethiopian Universities [ 48 , 49 , 52 , 96 , 97 ]. This variation might be due to variations in screening instruments and study populations.…”
Section: Discussioncontrasting
confidence: 73%
“…The overall prevalence of depressive symptoms was found to be 37.6%. This figure is higher than previous reports from Ethiopian Universities [ 48 , 49 , 52 , 96 , 97 ]. This variation might be due to variations in screening instruments and study populations.…”
Section: Discussioncontrasting
confidence: 73%
“…Anxiety, depression, and PTSD were jointly assessed through the Hopkins Symptom Checklist (HSCL-25) in one study [ 47 ]. Three other studies used the Depression, Anxiety, and Stress scale-21 (DASS) to collect data on these disorders [ 48 , 49 , 52 ]. Additionally, one study referred to anxiety, depression, and trauma as “common mental disorders” [20[p350]] (CMDs) experienced by vulnerable populations in developing countries exposed to emergencies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 studies that provided data on anxiety and handwashing with soap, six reported a positive correlation between handwashing with soap and anxiety, where participants with higher rates of anxiety were more likely to practice handwashing with soap [ 38 40 , 42 , 56 , 57 ]. Four studies found an inverse relationship in which those with higher rates of anxiety were less likely to wash their hands with soap [ 48 , 49 , 52 , 59 ]. One study found no direct relationship between anxiety and handwashing [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to conflicting information on social media during the pandemic may cause psychological difficulties [19,20] 47]. Anxiety was also reported by over one-third of students from various countries including Ethiopia [64], France [39,65], India [66], Israel [67], Jordan [68], Nigeria [69], the Philippines [70], Saudi Arabia [71], and the United Arab Emirates [72].…”
Section: Resultsmentioning
confidence: 99%